BUSINESS PROCESS REENGINEERING MODELING FOR ERP SYSTEM IMPLEMENTATION AT YOGYAKARTA SPECIAL PROVINCE HEALTH AGENCY - Feby Charlos; Lisdianto Dwi Kesumahadi; Bagus Setya (Journal of Innovation And Future Technology, 2026)
The implementation of Enterprise Resource Planning (ERP) systems in public health organizations is crucial for improving operational efficiency, integrating data, and enhancing service transparency. However, the challenges of digital transformation and bureaucratic processes require ongoing improvements through Business Process Reengineering (BPR). This study focuses on modeling the ERP system at the Health Agency of Yogyakarta Special Province, based on data from 2013–2014, and aligns it with Indonesia’s digital transformation initiatives in the health sector for 2025. Using a descriptive-analytic approach, the research employs BPR methodology to identify inefficiencies and propose optimized ERP workflows. The analysis includes process mapping, gap analysis, and functional modeling, ensuring alignment with national e-Government strategies.The findings show that the existing ERP system has effectively integrated data flows across administrative units. However, specific modules, especially in human resources and medical logistics, require reengineering to enhance real-time data exchange and decision-making. The study highlights the importance of combining ERP systems with BPR to continuously improve digital maturity and support data-driven governance in regional health institutions. This research contributes both a conceptual and practical framework for modernizing ERP systems within Indonesia’s public health sector, providing